Effects of dietary aflatoxin B1 on growth performance, body composition, haematological parameters and histopathology of juvenile Pacific white shrimp (Litopenaeus vannamei). (10th August 2015) - Zeng, S.L.; Long, W.Q.; Tian, L.X.; Xie, S.W.; Chen, Y.J.; Yang, H.J.; Liang, G.Y.; Liu, Y.J.
Abstract: An 8‐week feeding trial was conducted to evaluate the effects of dietary aflatoxin B1 (AFB1 ) on growth performance, haematological parameters and histological changes in juvenile Pacific white shrimp, Litopenaeus vannamei . Six practical diets (455 g kg ‐1 protein, 78 g kg ‐1 lipid) with different levels of AFB1 (0, 25, 50, 100, 500, 1000 μg kg −1 ) were formulated. Each diet was fed to triplicate groups of shrimps (initial weight: 0.52 g). The results showed that shrimp fed with control diet (0 μg kg −1 AFB1 ) had significant higher weight gain (WG) and specific growth rate (SGR) than other groups. However, there were no significant differences in feed efficiency (FE) or hepatosomatic index (HSI) among all groups. Compared to the control diet, AFB1 supplementation significantly changed the activities of shrimp serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), total antioxidant capacity (T‐AOC) and glutathione S‐transferase (GST) and the content of cholesterol (CHO). Histological damages were identified in the hepatopancreas of shrimp when dietary AFB1 level was over 107.6 μg kg −1 . Based on this study, it was concluded that the AFB1 level in Pacific white shrimp diet should be <38.1 μg kg −1 .